(untitled) (KULT_online, 2025)
The entanglements of environmental degradation, extractivist practices, and spatial marginalization have become central to discussions on ecological justice particularly within the context of the ‘Global South.’ In an attempt to further ‘globalize’ the application potential of the extractivist concept, Research Area 7: Global Studies and Politics of Space at the International Graduate Centre for the Study of Culture (GCSC) organized the one-day event “Spaces of Peripheralization: Extractivism, Pollution and Environmental Future in Southeastern Europe,” held on 22 May 2025, at Justus Liebig University Giessen. Organized by Ivana Dinić, Zekiye Gürün-Ücem, and Anna Ivanova in cooperation with the Chair of Southeast European History at JLU, the event brought together academic, visual, and activist perspectives to examine how ecological injustice in Southeastern Europe is shaped by legacies of state socialism, capitalist transformation, and uneven integration into European political and economic structures. Through a workshop, keynote lecture, and photography exhibition, the conference explored the lived effects of peripheralization, including the disproportionate distribution of environmental harm, the persistence of extractivist infrastructure, and the gap between environmental policy and local realities. By focusing on Southeastern Europe as a site of both historical rupture and ongoing ecological vulnerability, the event contributed to broader debates on sustainability, infrastructural violence, and the spatial inequalities within Europe.